A social history of the Ise shrines : divine capital - Teeuwen, Mark; Breen, John, 1956- (London ; New York : Bloomsbury, Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"Traces the history of the Ise shrines from the 7th century until today, focusing on the many episodes of crisis that transformed the social landscape around the shrines"--
First published
Includes bibliographical references and index.
AAL
Keywords: Ise Daijingū -- History; Religion and sociology -- Japan -- Ise-shi -- History; Ise-shi (Japan) -- History